Chito-Oligosaccharides: Derivations and Bio-Perspectives - Lokesh, S.; Chattopadhyay, Kasturi; Xavier, K. A. Martin (Chronicle of Bioresource Management, 2021)
Natural biopolymers are a potent reserve for ecologically safe food material. Being available from replenishable resources and higher biocompatibility and biodegradability, they fetch a huge demand to be exploited as a health constructive agent in several industries. Chito-oligosachharides are very short chained water soluble compounds, often called as chitosan oligomers or chitooligomers, prepared from partial hydrolysis of unstable glycosidic bonds of chitosan. Chemical and enzymatic hydrolysis are the two hydrolytic methods employed to prepare the oligomers from chitin and chitosan. Smaller molecular size, lower viscosity and greater solubility in aqueous solutions, have attracted the interest of many researchers to utilize them further for various biological applications including food and medicine. Inherent anti-microbial properties and film-formingabilityof chitin oligomers make it an ideal natural polymer that can be an alternative to chemically synthesized antimicrobial agents used in food industries.